Infant Nutrition: Overcoming Challenges in Malnutrition, Weaning, Allergies, and Food Storage for Healthy Growth and Development - Neelesh Kumar Maurya (International Journal of Trends in Horticulture, 2025)
This review paper examines the critical nutritional needs of infants, focusing particularly on the growth and development of children aged 6-12 months. During this phase, infants experience rapid physical, cognitive, and emotional development, which is heavily dependent on adequate nutrition. The paper explores various aspects of infant nutrition, including the roles of essential nutrients, the challenges posed by malnutrition, and the specific implications of protein energy malnutrition (PEM). It also covers the importance of weaning foods, which are introduced when a baby's growing nutritional demands cannot be met by breast milk or infant formula alone paper highlights the various weaning foods available, such as those based on cereals, legumes, and milk, and the importance of providing balanced, nutrient-dense options that support optimal growth. One of the major concerns discussed is the issue of malnutrition, particularly protein-energy malnutrition (PEM), which remains a global health problem, especially in developing countries. Infants and young children are especially vulnerable to PEM because their nutritional requirements are particularly high in relation to body weight during the early stages of life. The paper emphasizes the two primary forms of PEM, namely marasmus and kwashiorkor. Marasmus typically arises when infants are not provided adequate breast milk or complementary foods, resulting in extreme undernutrition. On the other hand, kwashiorkor is more commonly seen when a child is weaned off breast milk and relies mainly on starches, leading to deficiencies in protein. Both conditions have detrimental long-term effects on physical and cognitive development, and thus early intervention is critical. The study also explores how baby foods are changing. Over time, baby foods have become an essential part of infant diets, providing the necessary calories, vitamins, and minerals to support growth. These foods are designed for ease of consumption, often in the form of soft, pureed mixtures that can be swallowed easily. However, there are concerns regarding the affordability and accessibility of commercially available baby foods, particularly for families in lower-income brackets. To address this, there is growing interest in developing cost-effective and nutritionally balanced weaning foods that can be made from locally available ingredients, ensuring that infants receive the necessary nutrients without placing undue financial burden on families.
Keywords: : Infant nutrition; Baby Food; Food Allergies; Food Storage; Infant Growth; Kwashiorkor; Marasmus; Nutritional Needs; Protein Energy Malnutrition; Weaning Foods